The Influence of Word-of-mouth Advertising and Technological Innovations on The Customer Experience in E-Commerce. - Astiti, Nila; Hida Syahchari, Dicky; Agustina Situmorang, Soraya (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
E-commerce has replaced traditional retail, offering corporations financial savings and giving customers a streamlined experience enhanced by user-friendliness, customization, prompt customer support, and transaction security. Favorable consumer experiences facilitate word-of-mouth (WOM) promotion, which impacts purchasing choices and strengthens brand loyalty. Integrating advanced technologies, like artificial intelligence-powered customization and streamlined mobile applications, enhances consumer experiences, promotes brand loyalty, and facilitates efficient interactions. This research aims to examine the relationship between word-of-mouth advertising, technical innovation, and consumer experience in electronic commerce. The quantitative study methodology included a sample size of 120 individuals from the Greater Jakarta area, with data analysis conducted using SPSS. The findings demonstrate substantial beneficial effects of word-of-mouth (WOM) and technology innovation on consumer experience. The results indicate that e-commerce enterprises should allocate resources towards cutting-edge technology and promote good word-of-mouth to improve consumer experiences and sustain competition. Subsequent investigations should investigate supplementary variables such as service quality, customization, and the omnichannel experience.